REFRAMING CORPORATE SOCIAL RESPONSIBILITY: A THEOCENTRIC PERSPECTIVE THROUGH SHARIA ENTERPRISE THEORY - Setiawan Bin Lahuri; Alfi Khilmi Khusnia; Muchammad Taufiq Affandi (Ekonomi Islam, 2026)
Research aims: This study aims to critically examine the conceptual relationship between Corporate Social Responsibility (CSR) and Sharia Enterprise Theory (SET) as a normative-conceptual inquiry, focusing on corporate accountability, ethical responsibility, and the theological foundations of CSR. The study further explores how SET reconstructs CSR through a more comprehensive theocentric framework beyond conventional stakeholder-oriented approaches. Design/Methodology/Approach: This study uses a qualitative literature review and conceptual analysis, synthesizing secondary sources to reconstruct the theocentric foundations of corporate accountability. Research findings: This study synthesizes existing literature to demonstrate that conventional CSR, while normative and stakeholder-focused, remains constrained by anthropocentric assumptions and economic rationality. In contrast, the conceptual framework of SET reorients the center of accountability toward Allah as the ultimate stakeholder, integrating vertical (divine) and horizontal (human and environmental) dimensions. This synthesis highlights an ontological transformation that redefines corporate purpose from profit and sustainability toward amanah (trust), maslahah (public welfare), and falah (comprehensive well-being), thereby offering a more holistic CSR framework aligned with Islamic ethical and maqasid principles. Theoretical Contribution/Originality: This research contributes theoretically by positioning SET as an ontological and normative meta-framework that reconstructs CSR. It clarifies the theocentric basis of corporate accountability, providing a paradigm that transcends secular legitimacy and instrumental ethics, and establishes a maqasid-based evaluative lens for corporate performance. Practitioners/Policy Implications: For practitioners and policymakers, the study highlights the potential of integrating SET into corporate governance to achieve ethical, social, and environmental objectives aligned with Islamic principles. It suggests CSR should be operationalized not merely as a reputational or strategic tool, but as a manifestation of divine trust (amanah), guiding corporate decisions toward equitable wealth distribution and ecological sustainability. Research Limitations/Implications: This study is limited to a normative-conceptual and literature-based analysis without empirical validation or operational measurement of SET-based CSR. Future research is recommended to develop maqasid-based CSR indicators and conduct empirical studies in specific sectors, such as Islamic banking, to test the practical implementation and impact of the proposed framework.